A variação estilístico-pragmática sob a perspectiva do ensino reflexivo - Sousa, Fernanda Oliveira (2021)
This is the result of a research for a Professional Master in Letters reseachPROFLETRAS, about reflective teaching of linguistic variation, especially stylistic variation. As a product, this research presents a proposal didactic to be developed with students of the 6th grade of Elementary School, Phase II. We chose the workshop model. Five workshops are presented that deal respectively with: (i) linguistic variation in general; (ii) the stylistic variation in a comprehensive way; (iii) stylistic variation in speech; (iv) stylistic variation in writing; (v) monitoring and linguistic freedom. We base ourselves on the proposal of a Culturally Sensitive Pedagogy, by Erickson (1987); in Educational Sociolinguistics, BortoniRicardo (2005), (2009); in the Pedagogy of Linguistic Variation, Faraco (2008) and Bagno (2007); in the analysis of the speech and writing continuums, Marchuschi (2004); and in the Pedagogy of Autonomy, Freire (2019). In addition, the proposal is in line with the development of skills and competencies required by Common National Curriculum Base (BNCC). Because of the 19 Covid pandemic, the didactic proposal was not implemented, and therefore there is no analysis of the data collected. Instead we developed a dedicated notebook for teachers with guidelines and suggestions to them. We believe that this study can corroborate teachers in the teaching of Portuguese language and the formation of linguistically more competent individuals, protagonists of their interactions and aware of your choices.